Single-Cell Immunogenomic Approach Identified SARS-CoV-2 Protective Immune Signatures in Asymptomatic Direct Contacts of COVID-19 Cases - Sen, Kaushik; Datta, Sudeshna; Ghosh, Arup; Jha, Atimukta; Ahad, Abdul; Chatterjee, Sanchari; Suranjika, Sandhya; Sengupta, Soumya; Bhattacharya, Gargee; Shriwas, Omprakash; Avula, Kiran; Kshatri, Jayasingh; et al. (Frontiers in Immunology, 2021)
The response to SARS-CoV-2 is largely impacted by the level of virus exposure and status of the host immunity. The nature of protection shown by direct asymptomatic contacts of COVID-19 positive patients is quite intriguing. In this study, we have characterized the antibody titre, SARS-CoV-2 Surrogate Virus Neutralization, cytokine levels, single cell T-cell receptor (TCR) & B-cell receptor (BCR) profiling in asymptomatic direct contacts, infected cases and controls. We observed significant increase in antibodies with neutralizing amplitude in asymptomatic contacts along with cytokines such as Eotaxin, G-CSF, IL-7, MIF and MIP-1α. Upon scRNA sequencing, we explored the dynamics of the adaptive immune response in few representative asymptomatic close contacts and COVID-19 infected patients. We reported direct asymptomatic contacts to have decreased CD4+ naive T cells with concomitant increase in CD4+ memory and CD8+ Temra cells along with expanded clonotypes compared to infected patients. Noticeable proportions of class switched memory B cells were also observed in them. Overall, these findings gave an insight into the nature of protection in asymptomatic contacts.